Outcomes of Nd: YAG Goniopuncture After Viscocanalostomy/Phacoviscocanalostomy. Issue 6 (June 2016) - Mathews, Divya; Shirodkar, Amy-lee; Ahnood, Dana; Garrick, Adesuwa
Abstract : Purpose: The aim of this study is to evaluate the safety and efficacy of laser goniopuncture (LGP) to lower intraocular pressure (IOP) post-viscocanalostomy (VC)/phacoviscocanalostomy (PVC). Outcomes include: IOP reduction from pre-LGP levels and the need for further topical antiglaucomatous medication or surgery. Patients and Methods: A total of 541 eyes that underwent VC/PVC between 2009 and 2012, at the Stanley eye unit in Abergele were included in the study. Inclusion criteria: All patients who had LGP at any timepoint after VC/PVC when target IOP was not achieved +/− progression in visual field with at least 6 months of follow-up data. Statistical analysis was performed on IOP values pre- and post-LGP, involving χ 2, Fischer exact, Mann-Whitney U, and Wilcoxon tests. A P -value of <0.05 was accepted as the level of significance. Results: Of the 515 included eyes, 136 (26%) required LGP after a mean of 15.11±9.73 months after surgery (95% confidence interval, 13.46-16.76 mo), ranging from 1 to 42 months. LGP reduced IOP significantly from a mean of 22.92±5.80 to 17.08±5.30 mm Hg immediately for all eyes, a reduction of 5.84 mm Hg (or a 25% reduction) ( P <0.0001). IOP significantly reduced in the VC group with a mean reduction of 7.60 mm Hg compared with 4.85 mm Hg in the PVC group immediately after the procedure ( P =0.0038). LGP was required sooner in the VC group compared with PVC, 11.35 and 14.57 months, respectively ( P =0.0393). A total of 69 (62%) eyes were commenced on topical IOP-lowering medications, mean 7.26±6.41 months after LGP. Conclusions: This study supports previous evidence that LGP enhances the IOP-lowering success of VC/PVC. The advantages of LGP are that it is a minimally invasive clinic-based procedure with a low complication rate.